Hubungan Sistem Komunikasi, Kebutuhan Guru, dan Manajemen Penghargaan, Dengan Pengembangan Sumber Daya Manusia di Madrasah Aliyah Negeri Kepulauan Riau - Maryamah; Martinis Yamin; Lukman Hakim (Educompassion: Jurnal Integrasi Pendidikan Islam dan Global, 2025)
The development of human resources, particularly educators, is a crucial factor in improving the quality of education at Madrasah Aliyah Negeri Kepulauan Riau. However, its implementation faces several challenges, such as ineffective communication systems, suboptimal fulfillment of teachers' needs, and an unstructured reward management system. This study aims to analyze the relationship between communication systems, teachers' needs, and reward management with human resource development in madrasahs. The research employs a quantitative approach with a correlational survey design, involving respondents from educators at Madrasah Aliyah Negeri Kepulauan Riau. The findings indicate a positive and significant relationship between the three independent variables and human resource development. An effective communication system facilitates access to information and coordination in development programs, meeting teachers' needs enhances motivation and training effectiveness, and a well-structured reward management system boosts educators' enthusiasm. In conclusion, improvements in internal communication systems, the design of development programs aligned with teachers' needs, and the implementation of performance-based rewards are necessary to enhance the effectiveness of human resource development sustainably.